Pediatric Asthma Action Plans: National Cross-Sectional Online Survey of Parents' Perceptions - Pletta, Karen H; Kerr, Bradley R; Eickhoff, Jens C; Allen, Gail S; Jain, Sanjeev R; Moreno, Megan A (JMIR Publications, 2020)
BackgroundAsthma Action Plans (AAPs) are recommended for pediatric patients to help improve asthma control. Studies have shown variable results for unscheduled doctor and emergency room visits. AAPs may have an impact on parental self-efficacy for asthma management as well as on other daily living factors that are valuable for patients and families, such as the number of missed school days and parental workdays, and on school and caregiver management. ObjectiveThe purpose of this study is to understand parent perceptions of AAPs. The goals of this analysis were threefold, including examining (1) the association between pediatric AAPs and parental self-efficacy, (2) parent perceptions of the helpfulness of an AAP for daily living factors, and (3) associations with the type of provider who gave the AAP (a primary care provider or an asthma specialist). MethodsA national cross-sectional online survey was completed in October 2018 by parents of children with asthma aged 0-17 years. Survey questions included the presence or absence of a pediatric AAP, the Bursch Parental Self-efficacy for Asthma scale, parental perceptions of the AAP's helpfulness with regard to daily living factors ranked on a 5-point Likert scale, and the provider type who gave the AAP. Survey responses were summarized in terms of percentages or means and standard deviations. A 2-sample t test and analysis of covariance were used to compare self-efficacy for asthma and parental-perception-of-helpfulness scores between subjects with an AAP versus subjects without an AAP. All reported P values were 2-sided. ResultsA total of 704 parents with a child with asthma completed the survey. The parents had a mean age of 37.5 years (SD 10.9), and 82% (577/704) were women and 18% (127/704) were men. Most (564/704, 80%) parents had an AAP for their child; 65% (367/564) were written, 51% (286/564) were online, and 84% (474/564) were available at school. The Bursch Self-efficacy scale was significantly higher for parents with an AAP (mean 57.7, SD 8.6) versus no AAP (mean 55.1, SD 9.9; P<.001). Parents reported that they agreed/strongly agreed that an AAP was helpful for daily living factors, including managing asthma (446/544, 82%), decreased parental missed workdays (367/544, 68%), decreased child missed-school days (396/542, 73%), and for when a child is at school (422/541 78%), with other caregivers (434/543, 80%), doing normal activities (421/540 78%), and leading a normal life (437/540 81%). Parents agreed/strongly agreed that an AAP was helpful from all provider types: a pediatric provider (583/704, 82.8%), a family practice provider (556/704, 79%), and an asthma specialist (594/704, 84.4%). There was no significant difference (P=.53) between the type of provider who gave the AAP. ConclusionsParents who had pediatric AAPs for their children reported increased parental self-efficacy compared to those who did not have AAPs. Parents found AAPs helpful for decreasing missed time from work and school, and for asthma management when at home, school, and with other caregivers. Significant AAP helpfulness was seen regardless of the provider who gave the AAP, the parent's education, and income level. Findings support the usefulness of pediatric AAPs for families and the development of easily sharable electronic AAPs for children.